2021
DOI: 10.1021/acs.analchem.0c05459
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Peroxidase-Like Activity of Nitrogen-Doped Carbon Dots (N-CDs) Coupled with a Laminated Three-Dimensional Microfluidic Paper-Based Analytical Device (Laminated 3D-μPAD) for Smart Sensing of Total Cholesterol from Whole Blood

Abstract: This work presents a simple hydrothermal synthesis of nitrogen-doped carbon dots (N-CDs), fabrication of microfluidic paper-based analytical device (μPAD), and their joint application for colorimetric determination of total cholesterol (TC) in human blood. The N-CDs were characterized by various techniques including transmission electron microscopy (TEM), Xray photoelectron spectroscopy (XPS), and X-ray powder diffraction (XRD), and the optical and electronic properties of computational models were studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…The C 1s spectrum of DAC@PDA membrane (Figure 2d) showed four different peaks that were assigned to CC (284.6 eV), CN (285.5 eV), CO (286.3 eV), and CO (287.8 eV), respectively. [27] This further verified the formation of Schiff base between DAC and PDA. The highresolution scan XPS spectrum of Cu 2p (Figure 2e) displayed two Cu + characteristic peaks at 933.2 and 952.7 eV, [28,29] and other two peaks were associated with iodine (I) ion.…”
Section: Fabrication and Characterization Of Dac@pda/cu Membranementioning
confidence: 53%
“…The C 1s spectrum of DAC@PDA membrane (Figure 2d) showed four different peaks that were assigned to CC (284.6 eV), CN (285.5 eV), CO (286.3 eV), and CO (287.8 eV), respectively. [27] This further verified the formation of Schiff base between DAC and PDA. The highresolution scan XPS spectrum of Cu 2p (Figure 2e) displayed two Cu + characteristic peaks at 933.2 and 952.7 eV, [28,29] and other two peaks were associated with iodine (I) ion.…”
Section: Fabrication and Characterization Of Dac@pda/cu Membranementioning
confidence: 53%
“…3.02 mg/dl) [59], N-CDs (26.29 mg/dl) [22], AgNPs þ ChO x (1.55 mg/dl) [60] and Cu 2 (OH) 3 Cl-CeO 2 (1.93 mg/dl) [61]. For the visual detection using a smartphone, the previous literature reported the quantative detection of cholesterol in the range of 140e400 mg/dl, which used the standard test strips combined with mobile-phone imaging [12].…”
Section: Application As a Colorimetric Assay For Cholesterolmentioning
confidence: 99%
“…Further, Wang et al ( 2021) developed a full-wavelength coverage (blue to red) colorimetric sensor based on polymer-carbon nanodots for visual detection of nitrite via a smartphone APP [21]. Moreover, Nattasa et al ( 2021) reported mimicking peroxidase-like activity of nitrogen-doped carbon dots (N-CDs) coupled with a laminated three-dimensional microfluidic paper-based analytical device (laminated 3D-mPAD) for smart sensing of total cholesterol from whole blood [22]. However, these carbon-based materials have several shortcomings, such as susceptibility to aggregation, high detection limit, small linear range and low color sensitivity, which limit their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics based on cellulose, mainly including microfluidic paper-based analytical devices (μPADs) and microfluidic cloth-based analytical devices (μCADs), have caused rising interest due to the simple patterning methods and the ability to manipulate flow by the capillary wick force and not extra control pumps. 5,6 The hydrophilic channels are usually demarcated by hydrophobic barriers patterned on the substrates through photolithography, 7 wax printing, 8 inkjet printing, 9 screen printing, 10 laser treatment, 11 etc . Among them, wax printing technology by a wax printer is a popular and mass production-suitable approach to fabricate accurate wax patterns on paper.…”
Section: Introductionmentioning
confidence: 99%